Reconstruction and Development of Indonesian Language PAT Question Items Aspects of Class VII Literary Expression MTs N 1 Banjarnegara Academic Year 2021/2022 - Legi Aspriyanti; Risky Arbangi Nopi; Wangiran; Deby Luriawati Naryatmojo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Assessment in the 2013 curriculum is seen as having more complexity than the assessment system in the previous curriculum. So that in this study will discuss